Dal Caucaso al Mar d'Azov L'impatto dell'invasione mongola in Caucasia fra nomadismo e società sedentaria (1204-1295) - Lorenzo Pubblici (Scuole di dottorato, 2007)
This book is the attempt to bring - through the study of the written sources - one of the many faces of the complex Mongol history to its historical dimension. It concentrates on the Mongol dominion in Caucasia, considered as the area that goes from the Azov Sea down to modern Georgia. The period of the Mongol dominion was not the unique occasion during which sedentaries cultures and nomad civilizations came to interact; but it was only after this event that Caucasia underwent a coherent power of a united political system which enclosed in itself the character of both the social models. The genesis of this process and its results are the main object of this book.